DIE WAARSKOU-DEBAKEL (MET SPESIALE VERWYSING NA DIE SUID-AFRIKAANSE LUGMAG SE ROL) - Van Jaarsveldt, A.E. (Scientia Militaria - South African Journal of Military Studies, 2012)
By the summer of 1944 it was evident that the Allies were not to be denied their triumph in Europe. The approach of victory, however, created its own problems. Soviet assistance was highly valued by the Western Allies but it was becoming evi-. dent that they and the Soviet Union differed sharply over the new order to be imposed on the post-war world. This coolness between East and West was particularly marked in Poland. In Poland, Allied successes had strengthened the threa separate resistance movements which had developed during the course of the war. The most effective of the three was the Home Army, formed in 1942"which owed its allegiance to the London-based Polish Government-in-exile with its pro-Western sympathies. A second resistance movement, the People’s Army, had been launched by the Polish Communist Party in 1943. Although limited in size and effectiveneSs, it would provide a useful political instrument for the Soviets during the later stages of the war and in the post-war re-organisetion. Since the beginning of the German occupation, the leaders of the Polish resistance had dreamed of a national rising, the so-called "Big Scheme", whereby the Poles would rise and free themselves. Requests to launch such an operation were continually postponed by the Allies due to pressure on other war theatres, but by mid-1944, with the extraordinary progress made by the Russians in their advance from the east, it seemed feasible that such a rising could succeed. On 1 August 1944the Home Army under General Bor-Komorowski rose, and within the hour the whole city of Warsaw had followed suit. Despite immediate successes it was soon evident that large quantities of supplies would be needed if the resistance fighters were to have any chance of holding their own against the local German units. They immediately requested supplies from London and although the British Government was not able to comply with all their demands, it did consent to support the rising by dispatching 60 tons of supplies. It was one thing to supply resistanc forces in open country, but something entirely different to drop containers from a low altitude in the middle of a large city, in the midst of a battle, some 1 750 miles from the aircraft s’ home base. Air Marshal Siessor, commanding the British air forces in the Mediterranean, refused to regard the proposed flights as constituting a reasonable operation of war, and pressed his Government to approach the Russians, who would find aerial supply a relatively easy matter. The Soviet High Command, however, refused, branding the rising as merely opportunist and irresponsible. The whole task of delivering the supplies consequently fell to the Western Allies. In order to increase the number of sorties to Warsaw, 205 Group, Royal Air Force was asked to divert some of the Liberators of 31 Squadron, South African Air Force, and of 178Squadron, Royal Air Force, from their missions over southern France. On the night of 12 August the first large-scale airlift was flown to Warsaw. While this operation was regarded as successful, follow-up operations were, however, so disastrous that they could scarcely be sustained.